2022
DOI: 10.1002/acm2.13530
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based convolutional neural network for intramodality brain MRI synthesis

Abstract: Purpose The existence of multicontrast magnetic resonance (MR) images increases the level of clinical information available for the diagnosis and treatment of brain cancer patients. However, acquiring the complete set of multicontrast MR images is not always practically feasible. In this study, we developed a state‐of‐the‐art deep learning convolutional neural network (CNN) for image‐to‐image translation across three standards MRI contrasts for the brain. Methods BRATS’2018 MRI dataset of 477 patients clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In their study, the authors sought to generate synthetic post-contrast T1-weighted (T1w) scans from pre-contrast T1w and T2w scans, which yielded average whole-image SSIM values of 0.88 in their test set for their best-performing model. Moreover, several studies synthesizing T1w or T2w scans also reported similar SSIM values, often in the range of 0.85-0.95 ( 22 , 25 , 29 , 30 ). Therefore, it is encouraging that our whole-image SSIM values of 0.93 are comparable or even superior to those currently reported.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In their study, the authors sought to generate synthetic post-contrast T1-weighted (T1w) scans from pre-contrast T1w and T2w scans, which yielded average whole-image SSIM values of 0.88 in their test set for their best-performing model. Moreover, several studies synthesizing T1w or T2w scans also reported similar SSIM values, often in the range of 0.85-0.95 ( 22 , 25 , 29 , 30 ). Therefore, it is encouraging that our whole-image SSIM values of 0.93 are comparable or even superior to those currently reported.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, it warrants mentioning that the raw outputs of the DL model were often blurrier than their ground-truth counterparts. This effect has been widely documented in synthetic image studies ( 15 , 20 , 22 , 24 , 25 , 30 ), often driven by a lower spatial resolution input image up-sampled to match a higher spatial resolution output image. While this slight blurring effect is unlikely to affect underlying image quality (as evidenced by metric performance), in supplementary analyses we demonstrated that this difference was perceived by the clinicians and added bias to the analysis.…”
Section: Discussionmentioning
confidence: 90%
“…MRI synthesis approaches based on deep learning currently serve as an emerging field of research in neuro-oncology. 8,9 In particular, various deep learning-based approaches have been investigated for contrast-enhanced MRI synthesis toward reduction 7,[10][11][12][13] or even elimination 8,[14][15][16][17][18][19][20][21][22] of gadolinium contrast agents in glioma patients. The former involves methods that propose the synthesis of full-dose contrast-enhanced images from their low-dose counterparts (e.g., 10% low-dose).…”
Section: Introductionmentioning
confidence: 99%
“…One less routinely studied domain is synthetic image generation, i.e., mapping an input image to an output image. Recent work has highlighted the utility of DL for synthetically generating CT images from MRI sequences (14)(15)(16)(17)(18)(19)(20)(21), MRI sequences from CT images (22)(23)(24)(25)(26), and MRI sequences from other MRI sequences (27)(28)(29)(30)(31). However, to date, no studies have investigated the feasibility of using DL to generate high-resolution synthetic MRI sequences from low-resolution MRI sequences to decrease the required scan time for HNC-related imaging.…”
Section: Introductionmentioning
confidence: 99%